2022
DOI: 10.32872/cpe.6133
|View full text |Cite
|
Sign up to set email alerts
|

Coping in the Emergency Medical Services: Associations with the personnel’s stress, self-efficacy, job satisfaction, and health

Abstract: Background Emergency Medical Services personnel (EMSP) are recurrently exposed to chronic and traumatic stressors in their occupation. Effective coping with occupational stressors plays a key role in enabling their health and overall well-being. In this study, we examined the habitual use of coping strategies in EMSP and analyzed associations of coping with the personnel’s health and well-being. Method A total of N = 106 German Red Cross EMSP participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Mediation analyses: Do coping strategies mediate the relationships between individual and organizational soldier student factors and loneliness, life satisfaction, and COVID-19 stress? Expected relations between personality and organizational predictors and coping strategies (for personality see Connor-Smith and Flachsbart, 2007;Agbaria and Mokh, 2021; for organizational predictors see Srivastava and Tang, 2015;Portero de la Cruz et al, 2020;Rojas et al, 2022) are presented in Table 1 along with expected relations between coping strategies and psychological health outcomes (Deckx et al, 2018;Gori et al, 2020;Minahan et al, 2021;Zacher and Rudolph, 2021b;Kavčič et al, 2022). The respective expected indirect effects can be obtained by multiplying the two direct effects (i.e., two positive and two negative direct effects yield a positive indirect effect, one positive and one negative direct effect yield a negative indirect effect, and if at least one direct effect is zero, the indirect effect will be zero).…”
Section: The Present Studymentioning
confidence: 99%
“…Mediation analyses: Do coping strategies mediate the relationships between individual and organizational soldier student factors and loneliness, life satisfaction, and COVID-19 stress? Expected relations between personality and organizational predictors and coping strategies (for personality see Connor-Smith and Flachsbart, 2007;Agbaria and Mokh, 2021; for organizational predictors see Srivastava and Tang, 2015;Portero de la Cruz et al, 2020;Rojas et al, 2022) are presented in Table 1 along with expected relations between coping strategies and psychological health outcomes (Deckx et al, 2018;Gori et al, 2020;Minahan et al, 2021;Zacher and Rudolph, 2021b;Kavčič et al, 2022). The respective expected indirect effects can be obtained by multiplying the two direct effects (i.e., two positive and two negative direct effects yield a positive indirect effect, one positive and one negative direct effect yield a negative indirect effect, and if at least one direct effect is zero, the indirect effect will be zero).…”
Section: The Present Studymentioning
confidence: 99%
“…Moreover, social support and especially cognitive coping strategies have been found to relate positively to post-traumatic growth (Gurowiec, Ogi nska-Bulik, Michalska & Ke z dra, 2022). Acceptance is included in positive coping strategies, and thus, there can be a link to what Rojas et al (2022) have found. Acceptance was also found in this study in one of the subcategories under the "New perspectives and sensations" main category.…”
Section: Discussionmentioning
confidence: 95%
“…Acceptance is included in positive coping strategies, and thus, there can be a link to what Rojas et al . (2022) have found. Acceptance was also found in this study in one of the subcategories under the “New perspectives and sensations” main category.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous research has found that using personal resources, social support, cognitive strategies, and coping skills predict intimacy and conflict in ambulance workers’ romantic relationships (Shakespeare-Finch et al, 2002). Supporting the efficacy of prevention and interventions that supports EMS workers will support relationships and families (Rojas et al, 2022). In terms of clinical applications, clinicians should assess EMS workers’ partners for dysphoric arousal (e.g., trouble sleeping, difficulty concentrating, and ruminating thoughts) that may elucidate internal intrusions and PTSD symptomology related to STS.…”
Section: Implications For Practicementioning
confidence: 99%